Multiple Access Techniques for 5G Wireless Networks and Beyond - Vaezi, Mojtaba; Ding, Zhiguo; Poor, H. Vincent; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents comprehensive coverage of current and emerging multiple access, random access, and waveform design techniques for 5G wireless networks and beyond. A definitive reference for researchers in these fields, the book describes recent research from academia, industry, and standardization bodies. The book is an all-encompassing treatment of these areas addressing orthogonal multiple access and waveform design, non-orthogonal multiple access (NOMA) via power, code, and other domains, and orthogonal, non-orthogonal, and grant-free random access. The book builds its foundations on state of the art research papers, measurements, and experimental results from a variety of sources. Notably, it Includes orthogonal and non-orthogonal waveforms for 5G new radio and beyond: CP-OFDM, UF-OFDM, f-OFDM, WOLA, FBMC, and GFDM; Features NOMA via the power domain (fundamentals, clustering, power allocation, experimental trials, etc.) and the code and other domains (SCMA, IDMA, LDS-CDMA, PDMA, IGMA, RSMA, and RDMA); Outlines random access techniques (CSMA, CSMA/CD, ALOHA, slotted ALOHA, and LoRa), applications and use cases of 5G networks (eMBB, URLLC, mMTC, IoT, and V2V), as well as challenges and future directions in multiple access, random access, and waveform design.
Introduction to Cellular Mobile Communications -- OFDM Enhancements for 5G Based on Filtering and Windowing -- Filter Bank Multicarrier Modulation -- Generalized Frequency Division Multiplexing: A Flexible Multi-Carrier Waveform -- NOMA: An Information Theoretic Perspective -- Optimal Power Allocation for Downlink Non-Orthogonal Multiple Access Systems -- On the Design of Multiple-Antenna Non-Orthogonal Multiple Access -- Non-Orthogonal Multiple Access For Millimeter Wave Networks -- Full Duplex Non-Orthogonal Multiple Access Networks -- Heterogeneous NOMA with Energy Cooperation -- Performance Analysis of NOMA in Vehicle-to-Vehicle Massive MIMO Channels -- Sparse Code Multiple Access -- Interleave Division Multiple Access (IDMA) -- Pattern Division Multiple Access -- Grant-free Multiple Access Scheme -- Random Access versus Multiple Access -- Experimental Trials on Non-orthogonal Multiple Access (NOMA) -- Non-Orthogonal Multiple Access in LiFi Networks -- NOMA Based Integrated Terrestrial-Satellite Networks -- Conclusions and Future Research Directions for NOMA.
Keywords: Telecommunication; Wireless communication systems; Mobile communication systems; Computer networks .; Electric power production; Application software; Communications Engineering, Networks; Wireless and Mobile Communication; Computer Communication Networks; Electrical Power Engineering; Computer and Information Systems Applications